HUBUNGAN STATUS SOSIAL EKONOMI KELUARGA DENGAN PENERAPAN PHBS DALAM RUMAH TANGGA DI DESA KINALI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Guspita, Yusra; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research has intention to determine correlation between family socio economic status and phbs household application in kinali village kuantan mudik distric kuantan singingi regency. The research design is descriptive quantitative with systematic random sampling approach. Data collection method is questionnaire, interviews and direct observation. The analysis method is quantitative descriptive analysis presented in tables and then described in detail. The result indicates no significant correlation between family socio economic status and phbs household application in kinali village kuantan mudik distric kuantan singingi regency. Based on these results, it is recommended to improve hygienic and healthy behavior base on Principles of health.Keyword : Education, occupation, Income, Family, PHBS